Abnormal Functional Connectivity of Thalamic Subdivisions in Alzheimer's Disease: A Functional Magnetic Resonance Imaging Study. (1st August 2022) - Wu, Yue; Wu, Xingqi; Gao, Liying; Yan, Yibing; Geng, Zhi; Zhou, Shanshan; Zhu, Wanqiu; Tian, Yanghua; Yu, Yongqiang; Wei, Ling; Wang, Kai
Highlights: Decreased functional connectivity of the intralaminar and medial thalamus with the precuneus was observed in our patients, highlighting the different functions of each thalamic subdivision and different disease process for each subnucleus. Our results suggested that dysfunction of the intralaminar and medial thalamus is instrumental in Alzheimer's disease. Our findings could contribute to advancements in precision medicine, i.e., the fact that there is dysfunction in the functional connectivity of the intralaminar and medial thalamus with the precuneus could be considered in target-based therapy such as repetitive transcranial magnetic stimulation or deep brain stimulation. Abstract: Alzheimer's disease (AD) is characterized by global cognitive impairment in multiple cognitive domains. Thalamic dysfunction during AD progression has been reported. However, there are limited studies regarding dysfunction in the functional connectivity (FC) of thalamic subdivisions and the relationship between such dysfunction and clinical assessments. This study examined dysfunction in the FC of thalamic subdivisions and determined the relationship between such dysfunction and clinical assessments. Forty-eight patients with AD and 47 matched healthy controls were recruited and assessed with scales for multiple cognitive domains. Group-wise comparisons of FC with thalamic subdivisions as seed points were conducted to identify abnormal cerebral regions. Moreover, correlation analysis was conducted to evaluate the relationship between abnormal FC and cognitive performance. Decreased FC of the intralaminar and medial nuclei with the left precuneus was observed in patients but not in heathy controls. The abnormal FC of the medial nuclei with the left precuneus was correlated with the Mini Mental State Examination score in the patient group. Using the FC values showing between-group differences, the linear support vector machine classifier achieved quite good in accuracy, sensitivity, specificity and area under the curve. Dysfunction in the FC of the intralaminar and medial thalamus with the precuneus may comprise a potential neural substrate for cognitive impairment during AD progression, which in turn may provide new treatment targets.